Brand Equity, Brand Image Terhadap Customer Value Pada Lembaga Kursus Dan Pelatihan - Iradawaty, Sofiah Nur; Airlangga, Ichwan Bagus (FEB Universitas Sam Ratulangi Manado, 2021)
Courses and Training Institutions (LKP) need to develop themselves to the market so that they are able to survive in the face of increasingly high competitors due to the technological revolution and can still help the government provide solutions to social problems in the community through areas of expertise of interest and conduct competency tests or certification of abilities. of this study is to determine whether brand equity, brand image affect the customer value of LKP both partially and simultaneously. The approach used in this study is descriptive research through sample data with the Isaac and Michael approach and obtained a total sample of 133 people. The results of the study indicate that brand equity has no effect on customer value and brand image. Simultaneously, brand equity and brand image have a significant influence on customer value. The conclusion of this study is that the main problem in LKP is in the brand equity variable in dealing with its competitors and responding to existing market competition